2015
DOI: 10.1097/ccm.0000000000001139
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Outcomes, and Predictability of Critically Ill Obstetric Patients

Abstract: Patients spent a median of 7 days in hospital; 3.6% died. Maternal-fetal-neonatal mortality was determined not only by acuteness of illness but to social and healthcare aspects like education, prenatal control, and being cared in specialized hospitals. Sequential Organ Failure Assessment (during first 24 hr of admission), easier to calculate than Acute Physiology and Chronic Health Evaluation II, was a better predictor of maternal outcome. Evident health disparities existed between patients admitted to public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
53
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 41 publications
8
53
2
4
Order By: Relevance
“…46 The ICU cohort results show that the maternal mortality rate, main clinical conditions (hypertensive disorders of pregnancy), need for ICU technologies, blood transfusion, and organ system dysfunction were comparable with preceding studies from Latin America. 46 Whereas the overall perinatal mortality rate in the ICU was lower than in other high-income countries, 47,48 the NICU admission rate was comparable, 41,49 suggesting that mothers with severe acute maternal morbidity had a significantly greater proportion of premature newborns, which can affect perinatal outcomes including neonatal mortality and NICU admission. Because of the lack of power, we were unable to examine the influence of intimate partner violence on perinatal outcomes independent of the severe acute maternal morbidity.…”
Section: Controls (N = 112)mentioning
confidence: 99%
See 1 more Smart Citation
“…46 The ICU cohort results show that the maternal mortality rate, main clinical conditions (hypertensive disorders of pregnancy), need for ICU technologies, blood transfusion, and organ system dysfunction were comparable with preceding studies from Latin America. 46 Whereas the overall perinatal mortality rate in the ICU was lower than in other high-income countries, 47,48 the NICU admission rate was comparable, 41,49 suggesting that mothers with severe acute maternal morbidity had a significantly greater proportion of premature newborns, which can affect perinatal outcomes including neonatal mortality and NICU admission. Because of the lack of power, we were unable to examine the influence of intimate partner violence on perinatal outcomes independent of the severe acute maternal morbidity.…”
Section: Controls (N = 112)mentioning
confidence: 99%
“…Contradictory findings have been reported in relation to antenatal care use in women with severe acute maternal morbidity in the ICU from Latin American studies. 40,41 Since higher rates of intimate partner violence and suboptimal antenatal care were observed in women with severe acute maternal morbidity, it is possible that intimate partner violence may directly reduce access to antenatal care. In that regard, it was observed that antenatal care among Peruvian pregnant women exposed to intimate partner violence was diminished and delayed compared with nonabused women.…”
mentioning
confidence: 99%
“…27,28 In patients with HDP, intracranial hemorrhage (ICH) is associated with worse outcomes compared with ischemic stroke; in fact, ICH is one of the leading causes of maternal mortality associated with preeclampsia. 3,17,18,20,29,30 General Management in the Intensive Care Unit Key components of preeclampsia management in the ICU are delivery, corticosteroids for fetal lung maturation if the pregnancy is preterm, magnesium sulfate (MgSO 4 ) for prevention of eclampsia, antihypertensive medications, and appropriate use of fluids.…”
Section: Hypertensive Disease Of Pregnancymentioning
confidence: 99%
“…The most frequent causes of admission are due to obstetric diseases -those only occurring in pregnant/postpartum patients-as opposed to nonobstetric disorders, which can affect women who are not pregnant. 1,3 Critical care physicians are faced with the challenge of treating two patients in one and of managing specific obstetric disorders, not universally covered in formal critical care training. In fact, substandard care is one of the risk factors associated with maternal mortality.…”
mentioning
confidence: 99%
“…The researchers determined that the presenting conditions of these women were the same whether in developed or developing countries and ranged from 0Á7-13Á5 per 1000 births (Pollock et al 2010). Maternal mortality varies depending on social and healthcare determinants (Vasquez et al 2015) and is significantly higher in developing countries, but overall has been recorded as between 3-14% (Ashraf et al 2014, Ng et al 2014, Zwart et al 2014.…”
Section: Introductionmentioning
confidence: 99%